Increased Mortality in Schizophrenia Due to Cardiovascular Disease – A Non-Systematic Review of Epidemiology, Possible Causes, and Interventions - Ringen, Petter Andreas; Engh, John A.; Birkenaes, Astrid B.; Dieset, Ingrid; Andreassen, Ole A. (Frontiers in Psychiatry, 2014)
Background: Schizophrenia is among the major causes of disability worldwide and the mortality from cardiovascular disease (CVD) is significantly elevated. There is a growing concern that this health challenge is not fully understood and efficiently addressed. Methods: Non-systematic review using searches in PubMed on relevant topics as well as selection of references based on the authors experience from clinical work and research in the field. Results: In most countries, the standardized mortality rate (SMR) in schizophrenia is about 2.5, leading to a reduction in life expectancy between 15 and 20 years. A major contributor of the increased mortality is due to CVD, with CVD mortality ranging from 40-50% in most studies. Important causal factors are related to lifestyle, including poor diet, lack of physical activity, smoking and substance abuse. Recent findings suggest that there are overlapping pathophysiology and genetics between schizophrenia and CVD risk factors, further increasing the liability to CVD in schizophrenia. Many pharmacological agents used for treating psychotic disorders have side effects augmenting CVD risk. Although several CVD risk factors can be effectively prevented and treated, the provision of somatic health services to people with schizophrenia seems inadequate. Further, there is a sparseness of studies investigating the effects of life-style interventions in schizophrenia, and there is little knowledge about effective programs targeting physical health in this population. Discussion: The risk for CVD and CVD-related deaths in people with schizophrenia is increased, but the underlying mechanisms are not fully known. Coordinated interventions in different health care settings could probably reduce the risk. There is an urgent need to develop and implement effective programs to increase life expectancy in schizophrenia, and we argue that mental health workers should be more involved in this important task.